Chinese teachers’ perception of how TESOL differs from teaching EAP - Li, Yulong; Wang, Lixun (Universitas Pendidikan Indonesia, 2020)
The last two decades have witnessed a prolific increase in academic activity in the study of English for Academic Purposes (EAP). Many teachers who were trained for Teaching English to Speakers of Other Languages (TESOL) have been required to teach EAP. TESOL and EAP are two different concepts and teachers transitioning from TESOL to teaching EAP may encounter many difficulties. However, little research has been carried out in this area, particularly beyond the context of the UK. Helping teachers to clarify their perceptions of TESOL and EAP is the first step to facilitate this transition. The present study aims to facilitate Chinese university teachers’ pedagogical transitions from TESOL to teaching EAP by clarifying teachers’ own understanding of these two concepts and by outlining how several different factors contribute to their EAP conceptualisation. By using a multiple case study methodology, the current research has revealed that the investigated teachers’ perceptions of EAP comprised eclectic theories, which overlap with some current EAP literature. Facing a somewhat unethical research culture in China, some teachers added moral rubrics into their EAP concepts as reminders to their students. The teachers reported that TESOL and EAP diverged in discourses and commissions: EAP is more student empowering, but TESOL is more humanistic.